2020
DOI: 10.3389/fpsyg.2020.01030
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Cognitive Functions Following a Discrete Session of Competitive Esports Gaming

Abstract: Competitive organized electronic video gaming, termed "esports," has become an international industry. The physiological and cognitive health results of prolonged esport practice and competition have not been adequately studied. The current study examined physiological and cognitive changes after a session of esport gameplay for two types of games, first-person shooter and multiplayer online battle arena games. Increases in systolic blood pressure, increases in speed, and decreases in accuracy and inhibitory p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 15 publications
0
36
1
Order By: Relevance
“…Given that the median ISI score for the whole sample was equal to the clinical cut-off, the prolonged wakefulness could be explained by insomnia symptoms. Preliminary evidence suggests that esports athletes (particularly First Person Shooter competitors, which comprised our sample) can experience high stress levels [ 39 , 40 ], which is a common precipitant for insomnia symptoms [ 41 ], However, further research using more thorough diagnostic procedures (e.g., structured clinical interview) is necessary to determine insomnia prevalence rates in esports populations.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the median ISI score for the whole sample was equal to the clinical cut-off, the prolonged wakefulness could be explained by insomnia symptoms. Preliminary evidence suggests that esports athletes (particularly First Person Shooter competitors, which comprised our sample) can experience high stress levels [ 39 , 40 ], which is a common precipitant for insomnia symptoms [ 41 ], However, further research using more thorough diagnostic procedures (e.g., structured clinical interview) is necessary to determine insomnia prevalence rates in esports populations.…”
Section: Discussionmentioning
confidence: 99%
“…Özçetin et al (2019) compared processing speed between experts and non-experts for eSports by using the TMT, and they found that experts had significantly faster processing speed than non-experts. Also, Sousa et al (2020) found that the processing speed after the playing eSports was significantly faster than before. Thus, it indicated that processing speed is one of the factors required for eSports athletes.…”
Section: S500mentioning
confidence: 94%
“…According to Özçetin et al (2019), their study compared processing speed between experts and non-experts for eSports by using the Trail Making Test (TMT), and the result indicated experts had significantly faster processing speed than non-experts. In addition, Sousa et al (2020) examined processing speed by using the TMT for eSports athletes, and the results indicated the processing speed after the play was significantly faster than before the play. Thus, it indicated that processing speed is one of the factors required for eSports athletes, and it might be necessary to establish a psychological training method that enhances processing speed.…”
Section: Introductionmentioning
confidence: 99%
“…Movements of eSport athletes are usually constrained to keystrokes, gamepads, joystick, and mouse movements, which facilitates, compared to many real world sports, hypothesis testing and task manipulations typical of laboratory-based experimentation. Critically, virtual reality studies are routinely performed in both humans and animals and could be readily adapted to model eSport, which could be harvested toward a mechanistic understanding of motor performance ( Sousa et al, 2020 ). Whether eSport can be considered as a “true” sport is still debated ( Parry, 2019 ); however, it is worth mentioning that eSport-related activities are on the verge of being incorporated in future Olympics ( Grohmann, 2017 ).…”
Section: On the Definitions Of Sportmentioning
confidence: 99%